Pengaruh komposisi subtrat dari campuran kotoran sapi dan rumput gajah (Pennisetum purpureum) terhadap produktivitas biogas pada digester semi kontinu - Agus Haryanto; Rivan Okfrianas; Winda Rahmawati (Jurnal Rekayasa Proses, 2019)
This study aims to determine the effect of substrate composition on biogas production from a mixture of cow dung and elephant grass using semi-continuous digester. Fresh cow dung and elephant grass were obtained from Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Elephant grass was knife-chopped, crushed using a blender and then mixed with cow dung at a total solid (TS) ratio between elephant grass and cow dung varies from 35:65 (P1), 40:60 (P2), 45:55 (P3), and 50:50 (P4). This mixture was then diluted with tap water until its TS content reach 5% and was used as substrate. Four semi-continuous digesters (labeled as P1 to P4) having a capacity of 36 L and working volume of 28 L were initially loaded with 22 L of diluted fresh cow dung (dilution ratio of 1:1) as a starter (source of bacteria) and were left until stable condition. When the biogas was produced, the prepared substrate was added daily into the respective digester at a loading rate of 500 mL.d-1. Parameters to be observed included daily temperature and pH of the substrate, daily biogas production, TS and VS content, and biogas quality. The results showed that the digester worked at average pH of 6.9 and the daily temperature 26.3 to 29.7°C. The total biogas production for 60 days was 608.4, 676.8, 600.0, and 613.3 L, respectively for P1, P2, P3, and P4. Biogas yield after the substrate achieving the designed composition was 254 (P1), 260 (P2), 261 (P3), and 271 L.m-3 of the substrate (P4). The addition of elephant grass up to 50% could maintain high production of biogas.